The Problems, Potentials, and Resources of Disadventages Areas: Case Study Suranadi Village - Narmada, Lombok Barat, Nusa Tenggara Barat - Teja Kusuma, Trio Yonatahan; Dewi Vitama Pusfitasari; Yayuk Fitriani; Zulfatun Ni’mah (LP2M UIN Sunan Kalijaga, 2022)
Tourism is a sector that has great potential for economic and community development. However, in a pandemic situation, this sector experiences fatigue which also happens in Suranadi. This research is aiming for recommending tourism development in Suranadi as a preparation to face the post-pandemic tourism trend using the penta helix approach and BCG Matrix to show Suranadi’s position in the tourism market. The problem, potential, and resources of Suranadi are being identified to make a clear direction for tourism development. The method used in this research is qualitative and the data collected by observing, interviewing, and conducting a literature study about tourist attractions will be discussed. Based on the research, the direction of Suranadi's tourism development is to increase tourism innovation, empower local communities, develop tourism facilities and access, adapt to the post-pandemic era of life, promotion, and market, maintain quality and characteristics, and conduct tourism education.